Effect of Diabetes on Neurological and Cognitive Outcomes - Macko, Angelika; Wojciechowska, Urszula; Łuniewski, Bartosz; Nowicka, Iga; Dziemiańczuk, Jakub; Macedońska, Wiktoria; Morawska, Justyna; Olszanska, Monika (Quality in Sport, 2025)
Introduction: Diabetes mellitus significantly increases the risk of ischaemic stroke by accelerating atherosclerosis and small vessel disease in the brain, as well as increasing the incidence of atrial fibrillation. Its impact on haemorrhagic stroke, however, remains unclear. Hyperglycaemia worsens the prognosis after a stroke, limits neuroplasticity, and reduces BDNF levels. This leads to poorer functional performance and slower rehabilitation. Diabetes also increases the risk of dementia, including Alzheimer’s disease and vascular dementia, via metabolic disorders, endothelial dysfunction and neurodegenerative processes. This paper aims to provide an overview of the mechanisms linking diabetes with stroke, neurological prognosis and dementia risk. Materials and methods: A review of selected literature in the PubMed, Scopus, Web of Science and Google Schoolar databases was conducted, using the following keywords: “Diabetes mellitus”, “Ischemic Stroke”, “Cognitive impairment”, “Dementia”. Conclusions: Diabetes significantly increases the risk of ischaemic stroke by accelerating atherosclerosis and small vessel disease, and increasing the risk of atrial fibrillation. Its impact on haemorrhagic stroke, however, remains unclear. Hyperglycaemia worsens the clinical course and post-stroke prognosis by limiting neuroplasticity and regenerative processes. Diabetes also significantly increases the risk of dementia, including Alzheimer’s disease and vascular dementia, via a combination of metabolic disorders, vascular changes, and neurodegeneration. These findings highlight the importance of effectively controlling risk factors and intervening early to reduce the neurological burden associated with diabetes.